Chromosome-level genome assembly of the humpback puffer, Tetraodon palembangensis - Rui Zhang (GigaScience Press, 2021)
The humpback puffer, Tetraodon palembangensis, is a poisonous freshwater pufferfish species mainly distributed in Southeast Asia (Thailand, Laos, Malaysia and Indonesia). The humpback puffer has many interesting biological features, such as inactivity, tetrodotoxin production and body expansion. Here, we report the first chromosome-level genome assembly of the humpback puffer. The genome size is 362 Mb, with a contig N50 value of ∼1.78 Mb and a scaffold N50 value of ∼15.8 Mb. Based on this genome assembly, ∼61.5 Mb (18.11%) repeat sequences were identified, 19,925 genes were annotated, and the function of 90.01% of these genes could be predicted. Finally, a phylogenetic tree of ten teleost fish species was constructed. This analysis suggests that the humpback puffer and T. nigroviridis share a common ancestor 18.1 million years ago (MYA), and diverged from T. rubripes 45.8 MYA. The humpback puffer genome will be a valuable genomic resource to illustrate possible mechanisms of tetrodotoxin synthesis and tolerance.